Problem of Infant Feeding Practices: Implications for Immediate Action - Muzief Munir; I. Mustadjab; T.H. Rampengan; F.H. Wulur (Indonesian Pediatric Society, 1983)
A survey on infant feeding practice and its problems was conducted in an attempt to improve child health, particularly during the first two years of age, during which breast feeding should be the infant's main food. Allthough breast feeding was a generally accepted norm of infant nutrition durring the first year of age, the majority of infants were not breast fed after one year of age. It was clearly observed that early stopping of breast feeding, particularly during the first six months of age, not only increased the risk of malnutrition, but also increased the risk of diarrheal diseases, which in turn affected significantly the nutritional status. Early introduction of supplementary food, particularly around three months of age reduced the risk of malnutrition. Since the practice of breast feeding naturally decreases after six months of age, the improvement of the types and quality of supplementary food is important indeed, to maintain the beneficial effects of breast feeding.